Modelling an Efficient Three-Tier Fault Tolerance Approach for Resource Provisioning over Cloud - Suvarna Pawar; Y. Prasanth (EAI Endorsed Transactions on Cloud Systems, 2022)
INTRODUCTION: Nowadays, the cloud computing paradigm encounters newer challenges in offering fault tolerance methods during service provisioning. The failures during service provisioning are unavoidable in the large-scale heterogeneous network. Therefore, the adoption of appropriate fault tolerance techniques can improve the provided service's efficiency and reliability. OBJECTIVES: Thus, fault tolerating metrics give better accuracy to enhance the QoS, where the three-tier fault-tolerance approach is proposed to resolve the various failures in service provisioning. METHODS: Initially, a Collector Model collects the request and ranks it based on the service to be provided. Secondly, the redundancy filter module is designed to filter out the request replication and avoid the unnecessary process to be carried out. Finally, the fairness resource allocation module is designed to perform the prominent request received from the users based on the available resources without service congestion. RESULTS: This three-tier model operates concurrently to handle the multiple requests from the users of various connected nodes. The experimental analysis demonstrates that the three-tier fault tolerance model can enhance the cloud reliability over the large-scale heterogeneous network by ensuring QoS. CONCLUSION: The well-realized fault tolerance approach can efficiently demonstrate the structural model and fault tolerance process over the computing environment, therefore enhancing the cloud extendibility. Moreover, the computing environment's failure is hugely complex, and failure has to be handled efficiently.